$(G, \unicode[STIX]{x1D707})$-DISPLAYS AND RAPOPORT–ZINK SPACES. (19th July 2020) - Bültel, O.; Pappas, G.
Abstract : Let $(G, \unicode[STIX]{x1D707})$ be a pair of a reductive group $G$ over the $p$ -adic integers and a minuscule cocharacter $\unicode[STIX]{x1D707}$ of $G$ defined over an unramified extension. We introduce and study ' $(G, \unicode[STIX]{x1D707})$ -displays' which generalize Zink's Witt vector displays. We use these to define certain Rapoport–Zink formal schemes purely group theoretically, i.e. without $p$ -divisible groups.